Pendampingan Hak Cipta Produk UMKM dalam Upaya Meningkatkan Penjualan di Wilayah Banyumas - Ruhtiani, Maya; Naili, Yuris Tri (Nusantara Mengabdi Kepada Negeri, 2024)
This article focuses on enhancing the understanding and awareness of MSME in the Banyumas region about the critical importance of copyright protection. Additionally, it provides assistance in the copyright registration process to improve the competitiveness of their products. A key challenge for MSME business owners in Banyumas is the lack of intellectual property protection, which makes their innovative products vulnerable to imitation and misuse, diminishing their incentive to innovate further. The methodology adopted for this study includes data collection through observation and document analysis. The findings reveal that the program effectively enhanced the knowledge of MSME business owners regarding copyright protection and the associated registration process. Moreover, the mentoring process encouraged greater participation by MSME business owners in using copyright as a tool for product protection. This initiative not only helps safeguard their intellectual property but also has a positive impact on increasing sales and product competitiveness in the marketplace.